Different roughage to concentrate ratios in extruded ration and metabolic parameters of growing lambs - Oliveira, Karla Alves [UNESP] (2020)
The objective of this study was to evaluate the dry matter intake and metabolic parameters of 30 lambs fed with extruded ration with different roughage to concentrate ratios. It was carried out at the Federal University of Uberlândia from 7 December 2016 to 22 March 2017. The treatments were extruded rations, at 30% roughage and 70% concentrate (30R:70C) and 70% roughage and 30% concentrate (70R:30C) ratios, distributed completely randomly with two treatments and 15 animals per treatment. The treatment means were evaluated by the Tukey test and a regression study with a significance level of 5%. The dry matter intake (DMI) was evaluated. Blood was collected via jugular venipuncture to determine the concentration of energy-related, protein and mineral metabolites as well as enzymes indicative of hepatic and muscular activity. There was lower DMI for the 30R:70C treatment, as well as reduction in DMI in relation to body weight at the end of the experiment. The treatments influenced urea: animals with higher urea concentrations consumed the ration with higher concentrate content. Further, animals fed with more roughage had a higher concentration of phosphorus. In conclusion, the roughage to concentrate ratio of the extruded ration influenced the dry matter intake without triggering metabolic disorders in the animals.